Optimalisasi Peran Telekomunikasi dalam Mendorong Inovasi Pelayanan Publik di Era Digital: A Systematic Literature Review - Prasetyo, Muhammad Aliffarras; Veri, Jhon (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Innovations in telecommunications and networking have driven major transformations in public services, particularly in the health and education sectors. This study aims to explore the role of telecommunications technology in advancing public service innovation, especially in the digital era with the adoption of advanced technologies such as telehealth and e-government. Based on a search on Scopus on 25 August 2025, 1,567 articles were found using the keywords ‘Telecommunications,’ ‘network,’ ‘Innovation,’ and ‘service.’ Of these, 208 articles were selected for the period 2021-2025, comprising 102 document articles, 95 articles in English, and 54 open access articles. Through a systematic literature review (SLR) approach, this paper analyses the challenges and opportunities in applying telecommunications technology for public service innovation. The findings show that although technology improves efficiency and access, challenges such as the digital divide and privacy issues remain significant. This study provides policy recommendations to strengthen telecommunications infrastructure and address data security issues. The drive for innovation is particularly evident in telehealth, big data & AI-based health monitoring, 5G for remote areas, and open API-based e-government platforms to improve the efficiency of public services.